Professional Zakat in Indonesia: A Sentiment Analysis - Aisyah As-Salafiyah; Aam Slamet Rusydiana (International Journal of Zakat, 2023)
This study was conducted to review the perception of professional zakat in Indonesia within the scope of Islamic economics in terms of scientific research in published journals indexed by Dimension.ai that discuss the development of professional zakat. The method used is descriptive statistical analysis with meta-analysis and sentiment analysis from secondary data in the form of 71 papers published in the last 14 years, then processed using Ms. software. Excel 2016 and SentiStrength. The results show that research on professional zakat in the scientific literature has increased. The sentiment analysis results show that the differences of opinion among experts on professional zakat tend to be varied, with positive sentiment of 32%, negative sentiment of 27%, and the remaining neutral sentiment of 41%. This study is the first study to discuss the analysis of sentiment research on the theme of professional zakat with primary data.